Navigating backward, healing forward: The impact of retrograde EVLT in venous ulcer management: A case report - Sekarsari, Calysta Citra; Kurnianingsih, Novi; Kurniawan, Dea Arie (Universitas Brawijaya, 2025)
Background: Chronic venous insufficiency (CVI) is a condition caused by venous reflux (backward flow) or obstruction, leading to significant morbidity and negatively impacting patients' quality of life (QoL). One recognized treatment for CVI is Endovenous Laser Treatment (EVLT). The antegrade conventional approach of EVLT is typically straightforward, but distal vein access can sometimes be difficult to achieve. Case Illustration: A 50-year-old man presented with bilateral lower extremity swelling and a chronic ulcer on his left leg that had persisted for one year without improvement. Doppler ultrasonography confirmed CVI in both lower extremities, with a great saphenous vein (GSV) reflux time exceeding 1500 ms. The patient was diagnosed with CVI C6EpAsPr and underwent EVLT. However, the small diameter of the distal GSV and vasospasm made antegrade access challenging. A retrograde approach was employed for EVLT on his left lower extremity, resulting in a successful outcome. Conclusion: This case highlights the use of the retrograde approach in EVLT as a viable alternative for accessing distal lesions when antegrade access is difficult, leading to successful wound healing. The retrograde technique can be considered a valuable option for CVI patients facing such challenges.